Enhancing EFL College Students Listening Comprehension by Captioning - Kristin Rahayu (Universitas PGRI Semarang, 2015)
This study researched the impacts of English writings, Indonesian subtitles, or no subtitles on the tuning in appreciation of middle of the road and low-transitional level EFL students. A sum of 30 Grade-XII Taman Karya Vocational School of Purworejo understudies took part as in place bunches in the examination. The members saw the initial 19-min portion of the film Harry Potter and the Order of the Phoenix in just a single of the three entry conditions: English inscriptions, Indonesian inscriptions, or no subtitles and finished a 20-thing different decision listening understanding test. The consequences of ANOVA strategies exhibited that the understudies in every one of the three conditions performed correspondingly on the tuning in understanding test